2022
DOI: 10.1590/0103-6440202204653
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two alar cinch base suture in orthognathic surgery: a randomized clinical trial

Abstract: Le Fort I osteotomy is widely used in orthognathic surgery to correct maxillary deformities. However, this osteotomy may be related with the increase of alar base width. The aims of the present study were to compare two alar cinch suture after Le Fort I osteotomy and observe which type presents a better result in controlling the enlargement of the alar base after maxillary repositioning in orthognathic surgery. A randomized clinical trial was carried out with 40 patients randomly assigned in two intervention g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
(25 reference statements)
0
2
0
1
Order By: Relevance
“…In addition, the nasal base enlargement of patients undergoing Le Fort I osteotomy was evaluated, and two suture techniques of the wing cinch were compared, showing an increase in the alar base width in both groups, with a significant difference between the means. It was observed that the external technique better controlled alar base width after Le Fort I osteotomy [33].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the nasal base enlargement of patients undergoing Le Fort I osteotomy was evaluated, and two suture techniques of the wing cinch were compared, showing an increase in the alar base width in both groups, with a significant difference between the means. It was observed that the external technique better controlled alar base width after Le Fort I osteotomy [33].…”
Section: Resultsmentioning
confidence: 99%
“…Le Fort I osteotomy is the most used surgical technique to correct maxillary deformities and, despite the good skeletal results obtained, it causes a muscular detachment of the nasal region promoting enlargement of the nasal wing base [32]. External and internal suture techniques can be used to reconstitute the nasal wing base, and in particular, recent studies have shown that the external technique appears to be more effective than the internal technique in controlling wing base widening, although future studies are needed to confirm these findings [33].…”
Section: Clinical Studies On Humans' Evidence Of Orthognathic Surgery...mentioning
confidence: 99%
“…Una limitante importante para decidir entre las distintas técnicas es que ninguna de ellas tiene alto nivel de evidencia en cuanto a su efectividad, siendo la mayoría de los estudios encontrados de tipo descriptivo. Cabe destacar que para la cincha alar existen ensayos clínicos aleatorizados que respaldan su efectividad, pero estos son en contexto de ensanchamiento de la base nasal secundarios a osteotomías Le Fort I [30][31][32] .…”
Section: Discussionunclassified